On-site Sensor Noise Evaluation and Detectability in Low Cost Accelerometers - Manso, M. (2021)
Seismic networks help understanding the phenomena related with seismic events. These networks are employing low-cost accelerometers in order to achieve high-density deployments enabling accurate characterisation (high resolution) of strong earthquake motion and early warning capabilities. In order to assess the applicability of low-cost accelerometers in seismology, it is essential to evaluate their noise characteristics and identify their detectability thresholds. In this paper, a method is proposed that provides an indication of sensor noise, being demonstrated on different sensors. The method is designed to adapt to a sensor’s characteristics while on-site and in-operation, thus removing potentially related logistical and maintenance bottlenecks.